Why mothers attend playgroup - Harman, B.; Guilfoyle, Andrew; O'Connor, Moira (Early Childhood Australia, 2014)
While it is generally recognised that early childhood programs play an important role in increasing positive outcomes for children, families and society, there is very little research on the Australian playgroup experience and its role in providing support for mothers and addressing identity issues. The research aimed to fill this gap by asking why mothers attend playgroups and in particular what for them is the role of playgroup in supporting or challenging expectations of motherhood. Methods included one-on-one interviews with 11 mothers, aged 26 to 45 years, within the Perth metropolitan area with varied experiences with playgroups and follow-up focus groups with mothers who shared characteristic contexts or situations. The data showed there are three reasons that influence whether mothers will attend playgroup: to develop a sense of belonging; to seek validation as a mother; and, negative experiences of playgroup. This data is discussed in reference to positive and negative experiences, limitations of the study and future research.